Training Report on Water Accounting - Leh, Mansoor; Velpuri, Naga; Thilina, Prabath (2023)
The IWMI WA team and IWMI MENA conducted three days training December 5-7, 2022, for partners in Egypt on the use of the “Water Accounting Plus (WA+)” as part of the CGIAR regional integrated initiative: “From Fragility to Resilience in Central and West Asia and North Africa (#F2RCWANA)”. The aim of the initiative is to respond to the climate, nutrition and agrifood challenges most affecting the CWANA region. The F2R-CWANA Initiative is a 10-year Project implemented by International Water Management Institute (IWMI), ICARDA; International Center for Agricultural Research in the Dry Areas, IFPRI, World Fish, CIMMYT, CIP and ABC. The Initiative has five planned regional anchor countries – Egypt, Lebanon, Morocco, Uzbekistan and Sudan– representing different regional needs and a range of social contexts. The three day training was part of Work package 4 “integrated food, land, water and energy systems for climate-resilient landscapes”. The training was held in Cairo with 14 participants representing Engineers, researchers, ministry agents and Regional water resources and irrigation offices from Egypt, Lebanon, Jordan, Uzbekistan, Syria and Sudan (Annex 1). The training aimed to build partners capacity on the innovation “Water Accounting Plus (WA+)” as a decision-support tool developed by IWMI and its partners IHE, FAO to enhance water resources management, water productivity while reducing trade-offs. The training materials were prepared, and conducted by Dr. Mansoor Leh, Researcher, Dr Naga Velpuri, Senior Researcher and Mr. Prabath Thilina, Software Developer at IWMI which is a global leader in water accounting and water productivity applied and development research.